A study on design and safety aspect of basements / Nurulhuda Mohd Radzwan - Mohd Radzwan, Nurulhuda (Faculty of Architecture, Planning and Surveying, 2008)
This dissertation which titled “A Study on Design and Safety Aspect of Basement” is documented. The importance of design and safety aspect of basement is to define and clarify the problems of the basement. Otherwise, this research comprises the issues of design and safety aspect. For design are circulation of vehicles, parking space, type and level of basement. For safety aspect are flooding, ventilation, lighting and security system. In this research including of 6 chapters to completed it. This dissertation based on objective. To achieve the objectives of this dissertation should be to study on design aspect of basement to achieve the goals of comfort and safe. For instance, to identify the safety aspect at the basement to prevent problems likes flooding, ventilation, lighting, and security system. Then, know the facilities management to overcome problems at the basement. Observation, interview session, and questionnaires to the respondents are methods in this dissertation. Case study on MARA Headquarter at Jalan Raja Laut, Kuala Lumpur were undertaken to highlight the details information especially at the basement. It is documented in chapter 4. Literature review consist in chapter 2 and 3 were more on topics design and safety aspect issues.